Electrical Efficiency of Two-Stage Solid Oxide Fuel Cell Stacks with a Fuel Regenerator. Issue 11 (4th August 2020) - Nakamura, K.; Ide, T.; Kawabata, Y.; Nakajima, T.; Dohkoh, T.; Tsuji, M.; Akabane, S.; Hatae, T.
Abstract : Many studies have been conducted for the two-stage solid oxide fuel cell (SOFC) module. Since there are presently no studies for the fuel regenerator's effect on the electrical efficiency of the module to the best of the authors' knowledge, the effect of removing H2 O and/or CO2 was investigated. To estimate the electrical efficiency, models of the two-stage SOFC stacks with a fuel regenerator that use hydrocarbon or hydrogen fuel were used. The electrical efficiency was estimated by calculating the maximum fuel utilization rate and the cell voltage. The risk of carbon deposition from the regenerated anode off-gas was estimated by calculating the chemical equilibrium region of the anode gas. The maximum electrical efficiency had a net alternating current (AC) of 71.8% (lower heating value (LHV)) from methane fuel. This was obtained when 100% of the H2 O and CO2 were removed by the fuel regenerator. In addition, the net AC efficiency of 60.8% (LHV) was obtained from the 10% humidified hydrogen fuel when 98.0% of H2 O was removed by the fuel regenerator. These results suggest a high potential to generate a highly efficient power by the two-stage SOFC stacks with a fuel regenerator.